Cryogenic vacuum valve with actuation times down to 50 ms - Klimes, Jeffrey W.; Kanika; Krishnan, A.; Reich, Bianca; Anjum, Khwaish Kumar; Baus, Patrick; Birkl, Gerhard; Quint, Wolfgang; Schott, Wolfgang; Vogel, Manuel (Review of scientific instruments, 2023)
We have conceived, built, and operated a cryogenic vacuum valve with opening and closing times as short as 50 ms that can be used in strong magnetic fields and across a broad range of duty cycles. It is used to seal a cryogenic Penning trap at liquid-helium temperature for long-term storage of highly charged ions in a vacuum better than 10−15 hPa from a room-temperature ion beamline at vacuum conditions around 10−9 hPa. It will significantly improve any experiment where a volume at the most extreme vacuum conditions must be temporarily connected to a less demanding vacuum during repeated experimental cycles. We describe the design of this valve and show measurements that characterize its main features.